The Interplay Between the Intangible Cultural Heritage Label and Brand Types on Chinese Consumer Brand Responses - Xiao Huang; Qiulin Xu; Chen Gan (SAGE Open)
Intangible cultural heritage (ICH) elements are increasingly incorporated into brand marketing strategies to appeal to local consumers. However, little is known about the effect of ICH label on consumer brand responses. Drawing on cue utilization theory and social identity theory, this study examined the effects of ICH label and brand types (i.e., brand origin and brand positioning) on Chinese consumers’ brand attitudes and purchase intentions for brands incorporating Chinese ICH elements through the mediation role of cultural respect. This study tested the research hypotheses through three online experimental studies. Results revealed that attaching an ICH label (vs. without the label) to a brand’s ICH-inspired product significantly enhanced Chinese consumer brand responses, with this effect being more pronounced for foreign brands than domestic brands. These relationships were mediated by cultural respect. Additionally, this study explored the moderating role of foreign brand positioning and found that the ICH label was more effective for foreign mainstream brands than for luxury brands. This study provides evidence regarding the effectiveness of attaching an ICH label to improve consumers’ responses to brands utilizing ICH elements and to help weaken or eliminate local consumers’ in-group biased responses to foreign brands by considering various brand levels.